2001
DOI: 10.1034/j.1600-0749.2001.140505.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Melanin Content and Composition in Type V and VI Photoexposed and Photoprotected Human Skin: The Dominant Role of DHI

Abstract: A combination of techniques, including high-performance liquid chromatography (HPLC), spectrophotometric measurements, and a novel method for quantifying melanosome morphology, were applied to the analysis of melanin content and composition in highly pigmented (Fitzpatrick type V and VI) human skin. We found that total epidermal melanin content is significantly elevated in photoexposed type V and VI skin (approximately 1.6 x), while analysis of individual melanin components suggests that pheomelanin content in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 30 publications
7
58
1
2
Order By: Relevance
“…Another limitation of our study was that we used self-reported pigmentary phenotypes. Such assessment may miss certain aspects of pigmentary phenotypes influenced by these genetic variants, such as melanin content and composition 64, 65. In addition, misclassification is always a concern in epidemiologic studies.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our study was that we used self-reported pigmentary phenotypes. Such assessment may miss certain aspects of pigmentary phenotypes influenced by these genetic variants, such as melanin content and composition 64, 65. In addition, misclassification is always a concern in epidemiologic studies.…”
Section: Discussionmentioning
confidence: 99%
“…In human beings this pigment is made up of three different components: pheomelanin, of light yellow or red color, soluble in alkali; eumelanin rich in 5.6-dihidroxiindol-2-carboxylic acid (DHICA), of light brown color, soluble in alkali and eumelanin rich in 5,6-dihydroxiindole (DHI) of dark brown or black color. Thus, the wide range of skin tones and human hair are therefore the result of various combinations of the impact of those three factors (Alaluf et al, 2001). Preliminary studies in our laboratory demonstrated that commercial synthetic melanin (Sigmaโ€“Aldrich TM ) had an antifungal activity against Candida albicans and other Candida species, such as C. parapsilosis strain 22019, C. glabrata strain 2001, C. krusei strain 6258 (Fuentes et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is also a highly significant correlation between the concentrations of spherical melanosomes and pheomelanin [13]. Examining other racial types Alaluf et al [14,15] demonstrated that the most lightly pigmented types (European, Chinese and Mexican) have approximately half as much epidermal melanin as the most darkly pigmented skin types (African and Indian). However, the composition of the lighter skin types was comparatively more enriched with lightly colored alkali soluble melanin components (3ยท).…”
Section: Differences In Skin Colorationmentioning
confidence: 99%